Maternal near miss: as a tool for improving obstetric care: a 4.5-year audit from a tertiary referral centre in Sikkim - Kharka, Latha V.; Singhal, Bhawana; Pai, Muralidhar V.; Naren, Kadiyam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Maternal near-miss (MNM) audits are valuable tools for evaluating obstetric care and identifying gaps in the health system. Limited data are available from Sikkim, where a single tertiary centre caters to all six districts. This study aimed to assess the incidence of maternal near-miss and maternal mortality over a four and a half year period, and to implement the results for better maternal health. Methods: A retrospective observational study was conducted at a tertiary referral hospital in Sikkim, reviewing all deliveries between [2021-2025]. Maternal near-miss cases were identified. Indicators including MNM incidence ratio (NMIR), MNM to mortality ratio (MNM:MD), mortality index, and maternal mortality ratio (MMR) were calculated. Results: A total of 5,401 deliveries and 5,330 live births were recorded. There were 44 maternal near-miss cases and 8 maternal deaths. The NMIR was 8.25 per 1,000 live births, MNM:MD ratio was 5.5, and the mortality index was 15.4%. The calculated MMR was 150 per 100,000 live births. Compared to national figures (MMR ~93 per 100,000; NMIR ranging 3-17/1,000), the centre recorded a higher MMR and a moderate NMIR. Conclusions: The elevated MMR reflects referral nature of the institution, with most women presenting in moribund condition. The relatively lower NMIR suggests possible early recognition and prevention, but high mortality index underscores need for strengthening critical care, timely referral, and district-level facilities. Focused improvements in emergency obstetric management and referral systems are essential to reduce maternal morbidity and mortality.